Avaliação do hábito alimentar de uma população portadora de dia-betes mellitus tipo 1 - Lucia, Renata Paniago Andrade de (2009)
The importance of nutritional therapy in the type 1 diabetes mellitus (DM1) treatment has been emphasized since the beginning of its knowledge. However, studies evaluating the DM1 individuals eating habits, which could possibly subsidize more effective dietary guidelines, are still scarce. This work aimed at evaluating the DM1 patients eating habits. Fifty diabetic and seventy-seven non-diabetic patients, from both genders and older than fifteen of age, have been included. Customary diet has been assessed by means of the Food Frequency Questionnaire (FFQ), previously tested in pilot-population. It has been verified that the majority of diabetic individuals (82%) had between five and six meals per day and the majority of non-diabetic (54,5%) between three and four. Protein consumption (p<0,01) and fibers (p<0,01) were higher in the diabetic group and carbohydrates ingestion (p=0,01), simple sugars (p<0,01) and alcohol (p=0,04) within the non-diabetic group. There has been no difference between the aforementioned groups concerning cholesterol consumption, total fat, saturated and unsaturated although the total fat mean percentage presented was higher than recommended in both groups. The fiber intake was only adequate within the diabetic group. There has been a higher fruit and vegetable consumption among the diabetic patients, yet beneath recommendation. This study s data suggest that diabetic patients have healthier eating habits than the non-diabetic ones although the present some dietary mistakes, for instance high fat intake and lower than recommended fruit and vegetable ingestion beneath.